Поняття конституційного регулювання в сучасній науці конституційного права - Бабенко, К.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
The article investigates the contents of the constitutional regulation concept, as it is interpreted in a contemporary science of the constitutional law. The author analyzes various spheres of the constitutional regulation and points out the specific role of the political and legal relations in the process of the constitutional regulation.